HUBUNGAN PENGETAHUAN DAN PERSEPSI DENGAN STATUS GIZI BALITA DI PUSKESMAS PAAL MERAH I KOTA JAMBI TAHUN 2017 - Kristy Mellya Putri (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2018)
According to Susenas in 2005, the prevalence rate of under nutrition is 28%, and among those 8.8% suffer from malnutrition. It is estimated that there are still unreported (under reported) (Riskesdas, 2011). This research is quantitative descriptive conducted at Puskesmas Paal Merah I of Jambi City and has been implemented in June 2017. The population of this research is mother who have toddler who visited Puskesmas Paal Merah I Jambi from January to March 2017 as many as 768 people and the number of samples of 41 people with accidental sampling technique. Data collection with questionnaires, univariate and bivariate analyzes. The results showed that as many as 9 respondents (22.0%) had good knowledge, 22 respondents (53.7%) had enough knowledge, and 10 respondents (24,4%) had bad knowledge. A total of 27 respondents (65.9%) had positive perceptions, and as many as 14 respondents (34.1%) had a negative perception. A total of 31 respondents (75,6%) have good nutrition status of toddler, and as many as 10 respondents (24,4%) have less nutrition status. There is no correlation between knowledge with nutritional status of children under five at Puskesmas Paal Merah I. There is relationship between perception with nutritional status of children under five years old, with OR 43,200 (4,386 - 425,491). The results of this study is expected to provide health information and counseling about the nutritional status of toddlers by using language that is easy to understand and distribute brochures or leaflets and conduct discussions with respondents.